OPTIMALISASI PENGELOLAAN ASET SEBAGAI WUJUD REFORMASI BIROKRASI DI DAERAH - Maulidiah, Sri (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
One of the manifestations of the implementation of good governance principles as one of the demands of society is the realization of an adequate, informative, transparent and accountable regional wealth management system. Regional assets are an important component of local financial management. Management of assets / property of the region requires special attention because there is a significant increase in the value of assets / property of the region from year to year. Regional goods are goods purchased or obtained at the expense of APBD and goods derived from other legal proceeds, such as goods obtained from grants / donations, goods obtained as execution of the agreement / contract, goods obtained derived from the provisions of the Act , And goods obtained under a court decision that has obtained permanent legal force. Since the enactment of the balance sheeting policy as part of the government's financial statements, the recognition / assessment, and presentation and disclosure of regional assets / property become the main focus. This is because the assets / goods of local governments have a very significant and very complex value. Thus, efforts to increase accountability and transparency of local financial management can not be done without improving the management of assets / property owned by the region. As one important element to organize government and community service, the assets / property of the region must be managed properly and correctly. To manage properly and properly, the regional government must apply the principles of the Functional Platform, the Legal Certainty Principle, the Transparency Principle, the Efficiency Platform, the Accountability Principle and the Legal Certainity Principle. Important aspects of the management of government assets, in the form of; Planning of Needs and Budgeting of Assets / Regional Assets, Procurement of Regional Assets / Property, Security and Maintenance of Assets / Regional Property and Development, Supervision and Control of Assets / Regional Property.